Արձակ բանաստեղծության ժանրային առանձնահատկությունների շուրջ - Աստղիկ Բեքմեզյան (ՀՀ ԳԱԱ հրատ.)
Жанровые системы и их изучение одна из интересных сфер литературоведения. Стихи в прозе промежуточная жанровая форма, которую применяли такие известные поэты и прозаики, как Бодлер, Тагор, Тургенев, Мецаренц, Исаакян, Демирчян и другие. В статье рассматриваются тематические, структурные особенности жанра и выявляются специфика сюжета, лирического героя, пласты художественного языка. Genre systems and their study is one of the most interesting spheres of the literary criticism. Poems in prose is an intermediate genre form, which has been used by such well-known poets and prose writers like Baudelaire, Tagore, Turgenev, Metsarents, Isahakyan, Demirchian and others. The article examins thematic, structural features of the genre and identifies the specifics of the plot, the lyrical hero, layers of the literary language.
Keywords: Language and Literature